Significant impact of lithogenic dissolution from subantarctic volcanic islands on the regional marine silicon cycle - Edwin Cotard; Valentin Deteix; Frédéric Vivier; Arnaud Dapoigny; Sandrine Caquineau; Damien Cardinal (Limnology and Oceanography, 2025)
Silicic acid controls the production of diatoms, a predominant phytoplankton in the Southern Ocean. Diatoms are major contributors to the biological carbon pump, which is particularly active in the Southern Ocean as well as in areas naturally enriched in iron, such as around the Kerguelen Plateau. This study evaluates the factors controlling the biogeochemical cycle of Si and its dynamics in this area and how it is impacted by the island mass effect using the Si isotopic signatures of both dissolved and biogenic Si. While subsurface winter waters have similar δ 30 Si signatures and dissolved Si concentrations, surface δ 30 Si and dissolved Si values are different between stations. We show that this results from both (i) a different degree of dissolved Si utilization by silicifiers from winter water as the main Si source and (ii) an additional significant Si source to dissolved Si in the mixed layer from lithogenic Si dissolution for areas under the influence of the shelf. Indeed, the δ 30 Si DSi signatures near the islands are homogeneous and lighter by −0.33‰ ± 0.07‰ in the mixed layer compared to the outside plateau station. We estimate such lithogenic Si contribution to dissolved Si at 2.9 ± 1.8 μ mol L −1 for a corresponding specific flux of 3.7 ± 2.3 × 10 6 mol km −2 yr −1 in shallow areas around Heard and McDonald Islands (

Biogenic and lithogenic silicon along the GEOTRACES south West Indian Ocean section (SWINGS-GS02) and the islands mass effect on regional Si biogeochemical cycle - Valentin Deteix; Edwin Cotard; Sandrine Caquineau; William M. Landing; Frédéric Planchon; Thomas Ryan-Keogh; Damien Cardinal (Marine Chemistry, 2024)